Principle of Maximum Liability of Available Resources (MAR) in Regional Finance in Indonesia - Ansar Ansar; Zulkifli Aspan; Abdul Razak (Universitas Negeri Gorontalo, 2022)
One of the major resources in the regions is financial resources which are usually translated into the Regional Revenue and Expenditure Budget (APBD). In its management, it creates uncertainty about the fulfillment of human rights in regional financial management. This is because one of them is the regional financial regulation which causes the budget allocation for the issue of Economic, Social and Cultural Rights to be very inadequate. In this study, the authors used a normative research method by examining several regional regulations on APBD, using two approaches, namely the statutory approach and the conceptual approach. The research locations were selected in 6 regions, namely Bangka Belitung Islands Province, South Kalimantan Province, Malang City, Denpasar City, and Palu City. The author limits it only to economic, social and cultural rights in particular, the right to education, the right to health, the right to food, and the right to housing. Based on the results of the research, the authors propose that the government applies the Principle of Maximum Available Resources (MAR) in the management of regional finances, particularly in the budget for the fulfillment of economic, social and cultural rights.